Peran Badan Wakaf Indonesia dalam Mengembangkan Wakaf Ditinjau Dari Segi Maqashid Syariah - Faqih Hamdani Hafizh; Jaih Mubarok; Hari Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Until nowadays, waqf got attention from the government to develop in many ways of innovations. However, the enactment becoming main subject of waqf in law number 41/2004 has not been changed from twenty years ago covering the regulations of waqf in Indonesia. Many of economists having outlook amendment for this law in waqf. This research was held to assess the government role in developing waqf proccess, specifically Indonesian Waqf Board (BWI) as an independent institution authorized by the government to developing waqf in 2019-2023 period from “maqâshid sharia” point of view. This research used to the qualitative and descriptive method with library studies which used primary sources from laws of the Indonesia in waqf and laws that regulated BWI. The secondary sources taken from islamic classic books written by Ulama long time ago, results of seminars, journals, official reports, credible situs web, and result of interview with two members of BWI. The result of research appeared that the government as the authority and specifically BWI are being an important element in developing waqf which reach in “ad-dharuriyât” level in “maqâshid sharia”, and in common, the realisation BWI has been playing the role very well to develop waqf with various innovations.